Exploration the global single-cell ecological landscape of adenomyosis-related cell clusters by single-cell RNA sequencing - Lin, Jiajing; Liu, Li; Zheng, Fengque; Chen, Saiqiong; Yang, Weiwei; Li, Jingjing; Mo, Steven; Zeng, Ding-Yuan (Frontiers in Genetics, 2022)
Background: Adenomyosis (AM) is a common benign uterine disease that threatens the normal life of patients. Cells associated with microenvironmental immune ecology are crucial in AM, although they are not as well understood at the cellular level. Methods: Single-cell sequencing (scRNA-seq) data were used to construct an AM global single-cell map, to further identify relevant cell clusters and infer chromosomal copy number variation (CNV) in AM samples. The biological functions of cell clusters were explored and cellular evolutionary processes were inferred by enrichment analysis and pseudotime analysis. In addition, a gene regulatory network (GRN) analysis was constructed to explore the regulatory role of transcription factors in AM progression. Results: We obtained the expression profiles of 42,260 cells and identified 10 cell clusters. By comparing the differences in cell components between AM patients and controls, we found that significant abundance of endometrial cells (EC), epithelial cells (Ep), endothelial cells (En), and smooth muscle cells (SMC) in AM patients. Cell clusters with high CNV levels possessing tumour-like features existed in the ectopic endometrium samples. Moreover, the Ep clusters were significantly involved in leukocyte transendothelial cell migration and apoptosis, suggesting an association with cell apoptosis and migration. En clusters were mainly involved in pathways in cancer and apoptosis, indicating that En has certain malignant features. Conclusion: This study identified cell clusters with immune-related features, investigated the changes in the immune ecology of the microenvironment of these cells during AM, and provided a new strategy for the treatment of AM.